2014
DOI: 10.1038/ismej.2014.116
|View full text |Cite
|
Sign up to set email alerts
|

Water fleas require microbiota for survival, growth and reproduction

Abstract: Microbiota have diverse roles in the functioning of their hosts; experiments using model organisms have enabled investigations into these functions. In the model crustacean Daphnia, little knowledge exists about the effect of microbiota on host well being. We assessed the effect of microbiota on Daphnia magna by experimentally depriving animals of their microbiota and comparing their growth, survival and fecundity to that of their bacteria-bearing counterparts. We tested Daphnia coming from both lab-reared par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
132
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(143 citation statements)
references
References 48 publications
10
132
1
Order By: Relevance
“…Our experiments clearly showed that removing the microbiota of D. magna had an overall negative effect on host growth, survival and reproduction. Although in this study we used a newly developed method to obtain germ-free Daphnia without the use of antibiotics, results from non-nutritionally stressed treatments are similar to what Sison-Mangus et al (2014) found with respect to growth, survival and reproduction. This confirms the generality of the mutualistic relationship between Daphnia and its microbiota.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Our experiments clearly showed that removing the microbiota of D. magna had an overall negative effect on host growth, survival and reproduction. Although in this study we used a newly developed method to obtain germ-free Daphnia without the use of antibiotics, results from non-nutritionally stressed treatments are similar to what Sison-Mangus et al (2014) found with respect to growth, survival and reproduction. This confirms the generality of the mutualistic relationship between Daphnia and its microbiota.…”
Section: Discussionmentioning
confidence: 56%
“…showed that inoculating germ-free Daphnia with these bacteria had a positive effect on host fitness, although for Limnohabitans sp. this was found to be restricted to specific strains (Sison-Mangus et al, 2014;Peerakietkhajorn et al, 2015b). Interestingly, the dominant Aeromonas sp.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies in the past have shown that microbiota not only provides fitness benefit to the host but also plays a significant role in its reproduction [13]. To our knowledge, this is the first study reporting clear changes in microbial content during asexual reproduction and sexual maturity indicating microbial influence over a major life event.…”
Section: Discussionmentioning
confidence: 73%
“…An increase in the density of zooplankton monocultures during their cultivation on RAS waste water could represent the bacterial flora in this water, that serves an additional feed element for crustaceans and contributes to their reproduction [20].…”
Section: Fig 2 Density Dynamics Of Zooplankton Cultures During Cultmentioning
confidence: 99%